2022
DOI: 10.1002/ddr.21920
|View full text |Cite
|
Sign up to set email alerts
|

Daphnetin inhibits the survival of hepatocellular carcinoma cells through regulating Wnt/β‐catenin signaling pathway

Abstract: Evidence has demonstrated that Daphnetin has antiangiogenesis activity, indicating it might be a new multi-targeted medication for cancer therapy. Here, we aimed to reveal Daphnetin role in hepatocellular carcinoma (HCC) progression and the underlying mechanism. Huh7 and SK-HEP-1, two human HCC cell lines were used in this study. MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide), colony formation, flow cytometry, and tumor-bearing experiments were applied to evaluate the effects of different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In in vitro studies on two hepatocellular carcinoma cell lines (Huh7 and SK-HEP-1), daphnetin inhibited cell viability and promoted apoptosis. The obtained IC 50 doses of daphnetin against the tested hepatocellular carcinoma lines Huh7 and SK-HEP-1 were 69.41 and 81.96 μM, respectively [ 38 ]. The IC 50 values of daphnetin in this study ranged from 40.48 ± 10.90 µM to 183.97 ± 18.82 µM and are comparable to those obtained against hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In in vitro studies on two hepatocellular carcinoma cell lines (Huh7 and SK-HEP-1), daphnetin inhibited cell viability and promoted apoptosis. The obtained IC 50 doses of daphnetin against the tested hepatocellular carcinoma lines Huh7 and SK-HEP-1 were 69.41 and 81.96 μM, respectively [ 38 ]. The IC 50 values of daphnetin in this study ranged from 40.48 ± 10.90 µM to 183.97 ± 18.82 µM and are comparable to those obtained against hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Above this concentration, a slight cytotoxicity of daphnetin was observed. Other in vitro experiments confirmed that low concentrations of daphnetin (up to 100 µM) did not affect the viability of normal cells such as normal liver cells (WRL68 line), primary hepatocytes (PH), human normal intestinal epithelial cells (NCM460) and gastric mucosal cells (GES-1) [ 38 ]. In the case of osteoblasts, daphnetin showed no cytotoxicity, but it enhanced cell proliferation, differentiation and mineralization by activating the Wnt/GSK-3β/β-catenin signaling pathway [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, daphnetin (25 and 50 mg/kg) is reported to exert antitumor effects by inhibiting the Wnt/β-catenin signaling pathway in hepatocellular carcinoma xenograft models ( Liu C. et al, 2022 ). The roles of daphnetin in apoptosis and G1 phase arrest of hepatocellular carcinoma cells were potently neutralized by activation of the Wnt/β-catenin signaling with SKL2001 treatment, which is an agonist of the Wnt/β-catenin signaling pathway ( Liu C. et al, 2022 ).…”
Section: Effects Of Daphnetin On Signaling Pathwaysmentioning
confidence: 99%
“…DAP suppressed the cell viability and tumorigenesis, promoted the apoptosis of cells, and induced the arrest the cells in G1 phase dose-dependently which were rescued by SKL 2001, an activator of Wnt/β-catenin signaling. Thus, DAP exerted an antitumor role through the inactivation of Wnt/β-catenin signaling ( Liu et al, 2022 ).…”
Section: Pharmacological Activities Of Daphnetinmentioning
confidence: 99%